Comparison of the Effect of Abdominal Massage and Hugo Point Acupressure on Infantile Colic Symptoms - Khadijeh Moghaddam; tahereh sadeghi; ali Khakshour; ali Khorsand Vakilzadeh; Ahmad Shah Farhat (Mashhad University of Medical Sciences, 2022)
Background: Infantile colic is observed in healthy infants less than three months of age. Excessive crying in these infants leads to fatigue and maternal anxiety.Aim: The present study aimed to compare the effect of abdominal massage and Hugo point acupressure on the symptoms of infantile colic.Method: In this clinical trial study, 144 infants were selected via convenience sampling and randomly assigned to three groups of abdominal massage, Hugo point acupressure, and control. The infants in two groups of abdominal massage and Hugo point acupressure received the interventions three times in the evening, while the control group only underwent the routine training. The duration of colicky crying and sleep duration per 24 hours was recorded for four weeks. At the end of four weeks, the Infant Colic Scale (ICS) was completed in three groups. Three groups were compared using the Wilcoxon test.Results: The mean difference scores after the intervention in comparison with that before the intervention were obtained at -6.62±4.84, -3.55±3.12, and -3.92±4.02 in Hugo point acupressure, abdominal massage, and control groups, respectively. This difference was statistically significant (P<.05). The three groups of Hugo point acupressure, abdominal massage, and control significantly differ in terms of mean scores of sleep time in four weeks (P<001). There was a significant difference between the mean scores of crying duration in the second, third, and fourth weeks (P <0.001).Implications for Practice: Hugo point acupressure had a more significant effect on the alleviation of colic pain, as compared to abdominal massage and changing position. Furthermore, acupressure shortened the duration of crying and prolonged sleep. The development of acupressure training programs for mothers is recommended as a simple method for the treatment of infantile colic.